Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1061/(asce)cc.1943-5614.0000740
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Glass Fiber–Reinforced Polymer Reinforced Concrete Continuous T-Beams

Abstract: In this study, a total of twelve beams continuous over two spans of 2,800 mm each were constructed and tested to failure. The beams were divided into two series. Series 1 included six T-beams under symmetrical loading, while Series 2 dealt with six rectangular beams under unsymmetrical loading conditions. In Series 1, the test variables included material type, assumed percentage of moment redistribution, spacing of lateral reinforcement in flange, arrangement of shear reinforcement, and serviceability requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…By using Equations (2) and (3), the storage and loss moduli are expressed as Equations (4) and (5), respectively. The ratio of loss modulus to storage modulus is defined as loss factor (Tanδ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using Equations (2) and (3), the storage and loss moduli are expressed as Equations (4) and (5), respectively. The ratio of loss modulus to storage modulus is defined as loss factor (Tanδ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the storage modulus of abovementioned nanocomposite was higher than those of pure polypropylene and polypropylene/glass composite. [5] Karipal et al added the nanoclay to epoxy/glass composite and observed that the tensile and flexural strengths and moduli increased. [6] Poly(butylene terephthalate) (PBT) is an important engineering thermoplastic, which due to its distinctive properties comprising high crystallization rate, excellent strength and stiffness, good creep and fatigue resistances, good thermal stability and electrical properties, is widely used in numerous applications.…”
Section: Introductionmentioning
confidence: 99%
“…Due to FRP advantages compared to steel bars (high strength to weight ratio and durability), the use of FRP instead of steel as internal reinforcement for concrete elements has become increasingly common, especially in North America, as a means to avoid steel corrosion problems. Flexural behaviour of RC beams reinforced with FRP bars is investigated in previous researches [1][2][3][4][5][6][7][8][9][10]. Flexural ductility of RC elements with steel bars is calculated as the ratio of ultimate displacement to displacement at steel yield, while in the case of RC elements reinforced with FRP bars it can be calculated in a number of ways [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the case where the failure of strengthened members is due to the NSM system failure, two different types of rupture are possible, the failure is due to the pull-out of the rods inducing almost splitting of the resin and concrete surrounding the groove or the peeling-off of the concrete covering the groove from the end of the rod [6]. Although many in situ RC beams are of continuous construction, there has been very little research into the behaviour of such beams [7][8][9][10][11]. However, moment redistribution in such elements was reported in previous studies [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although many in situ RC beams are of continuous construction, there has been very little research into the behaviour of such beams [7][8][9][10][11]. However, moment redistribution in such elements was reported in previous studies [12][13][14][15][16][17][18][19]. The observed moment redistribution was attributed to the relatively low modulus of elasticity of the FRP bars, compared to that of steel bars, the plasticity of concrete at high-load levels and the different bond characteristics of the FRP bars, in addition to the difference in the flexural stiffness between the critical sections.…”
Section: Introductionmentioning
confidence: 99%